Comparison of Autorefractors and Retinoscopy with Subjective Corrections in Myopia and Hypermetropia - G , Taarika; Divya, N; Ramakrishnan, Abinaya (International Journal of Membrane Science and Technology, 2023)
Introduction: Since Autorefractors nowadays have become mainstream and available in almost all clinical setups Autorefractors to make measurements swiftly. So in such a situation , it is necessary to compare the results of different refraction measurement devices including Autorefractors and retinoscopy with subjective corrections in Myopia and Hypermetropia. Methods: This is a descriptive study done among 100 patients visiting Ophthalmology OPD with Myopia and Hypermetropia in Saveetha medical college selected by convenience Sampling . The data collect ed will be tabulated and analyzed using SPSS. Results: Patients were divided into two age groups to find out age wise distribution of type of refractive errors and comparing the results from the subjective examination and results given by the Autorefractive meter it is clearly from this study that the difference between two methods was almost negligible and that Autorefractors are also a reliable method of measurement in a large clinical setup. But, on the other hand, manual retinoscopy still prove to be far better and efficacious technique yielding accurate results when it is used to check for refractive errors in individuals. Conclusion: In this study, we conclude that autorefractors are also reliable and can also be used to estimate refractive errors in a clinical setup, even though manual retinoscopy remains the most accurate and efficacious method..